Continuously hierarchical nanoporous graphene film for flexible solid-state supercapacitors with excellent performance. (June 2016) - Qin, Kaiqiang; Kang, Jianli; Li, Jiajun; Liu, Enzuo; Shi, Chunsheng; Zhang, Zhijia; Zhang, Xingxiang; Zhao, Naiqin
Abstract: Continuously hierarchical nanoporous graphene (hnp-G) films are synthesized by a combination of low-temperature CVD growth of hydrogenated graphite (HG) coating on nanoporous copper (NPC) and rapid catalytic pyrolysis of HG at high temperature. Low-temperature growth of HG coating on NPC can obviously delay the coarsening evolution of NPC at high temperature, providing the precondition to obtain hnp-G with small pore size (1–150 nm) by catalytic pyrolysis at high temperature. The high specific surface area (1160 m 2 /g) of hnp-G are mainly originated from the external surface (954.7 m 2 /g), resulting in fully accessible channels for ion transport. More importantly, the continuously 3D hierarchical nanoporous structure and fully wettability of the hnp-G with gelled electrolyte not only effectively prevent the restacking of graphene even under dramatic squeezing but also guarantee the continuous and short electron/ion diffusion pathway in the whole electrodes, resulting in ultrahigh specific capacitance (38.2 F/cm 3 based on the device) and excellent rate performance. The symmetric SC offers ultrahigh energy density (2.65 mW h/cm 3 ) and power density (20.8 W/cm 3 ) and exhibits almost identical performance at various curvatures and excellent lifetime (94% retention after 10, 000 cycles), suggesting its wide application potential in powering wearable/miniaturized electronics. Highlights: Free-standing hierarchical nanoporous graphene (hnp-G) film was successfully fabricated by a simple method. The symmetric solid-state supercapacitor, assembled using two pieces of hnp-G films, offers ultrahigh energy and power densities and exhibits almost identical performance at various curvatures and excellent lifetime.